9(x+1)-3x=2(3x+1)-4

Simple and best practice solution for 9(x+1)-3x=2(3x+1)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+1)-3x=2(3x+1)-4 equation:


Simplifying
9(x + 1) + -3x = 2(3x + 1) + -4

Reorder the terms:
9(1 + x) + -3x = 2(3x + 1) + -4
(1 * 9 + x * 9) + -3x = 2(3x + 1) + -4
(9 + 9x) + -3x = 2(3x + 1) + -4

Combine like terms: 9x + -3x = 6x
9 + 6x = 2(3x + 1) + -4

Reorder the terms:
9 + 6x = 2(1 + 3x) + -4
9 + 6x = (1 * 2 + 3x * 2) + -4
9 + 6x = (2 + 6x) + -4

Reorder the terms:
9 + 6x = 2 + -4 + 6x

Combine like terms: 2 + -4 = -2
9 + 6x = -2 + 6x

Add '-6x' to each side of the equation.
9 + 6x + -6x = -2 + 6x + -6x

Combine like terms: 6x + -6x = 0
9 + 0 = -2 + 6x + -6x
9 = -2 + 6x + -6x

Combine like terms: 6x + -6x = 0
9 = -2 + 0
9 = -2

Solving
9 = -2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4(s+1)=12(s+3) | | 18-4x=-36 | | 10x+5(x-3)=15 | | 4e^16x=14 | | 6x-12=2x+36 | | -24y-42=18 | | s+14=17-5s | | 7n^2+2=9n | | 8c+30=10c | | -x-62=136-12x | | 42=7j-28 | | 148-4x=5x*22 | | 3(4.8x+10)=2x+5.4 | | 5-(n-3)=-1+2(n-3) | | 0.625m-0.375=0.5m+0.875 | | 6x+21=2x+9 | | 1a-8=6-2a | | 27f=81 | | 12b+9=2b+8 | | 9x-4(x-3)=x+120 | | 23x+47=12 | | 36=6y+9x | | -18x-42=8x-16+16 | | 3t+31=-56 | | 6x+62=2x+30 | | 7n^2+19n=6 | | 3b+4/3=b-4/2 | | -5(x+3)-16=12+2 | | -.5=.5-1 | | 4x^2-19x+39=5x+4 | | b-1+b-1+b+3+2b=31 | | 17n^2+19n=6 |

Equations solver categories